Rapid Microfluidic Assay for the Detection of Botulinum Neurotoxin in Animal Sera - Babrak, Lmar (Toxins (Basel), 2016)
Potent Botulinum neurotoxins (BoNTs) represent a threat to public health and safety. Botulism is a disease caused by BoNT intoxication that results in muscle paralysis that can be fatal. Sensitive assays capable of detecting BoNTs from different substrates and settings are essential to limit foodborne contamination and morbidity. In this report, we describe a rapid 96-well microfluidic double sandwich immunoassay for the sensitive detection of BoNT-A from animal sera. This BoNT microfluidic assay requires only 5 μL of serum, provides results in 75 min using a standard fluorescence microplate reader and generates minimal hazardous waste. The assay has a <30 pg·mL(−1) limit of detection (LOD) of BoNT-A from spiked human serum. This sensitive microfluidic BoNT-A assay offers a fast and simplified workflow suitable for the detection of BoNT-A from serum samples of limited volume in most laboratory settings.